Agent-Based Modelling of Interstellar Contacts Using Rumour Spread Models - Uyar, Tevfik; Özel, Mehmet Emin (Cambridge University Press, 2020)
Some stochastic model of rumours asserts that even an advanced communication network does not guarantee every agent hears certain news because they predict that rumour spreaders convert to stifflers when contacted with an informed agent. In this study, we adapted two rumour spread models to interstellar communication by developing an agent-based model (ABM) for exploring the issue more rigorously. We enhanced the spread models by adding two additional parameters called conversion probability and stop-criterion, which represent the eagerness and persistency of civilizations to establish new contacts. Results of the ABM under several settings suggest that limited SETI searches lead to undiscovered civilizations. Earth may be one of these undiscovered civilizations although an advanced communication network might already be set up. Hence, we speculate that rumour spread models can propose another solution to Fermi's Paradox.
Keywords: Agent-based Model; Fermi's Paradox; Rumour Models